THE EFFECT OF FEAR OF MISSING OUT (FOMO) AND ELECTRONIC WORD OF MOUTH (EWOM) ON PURCHASE INTENTION WITH BRAND IMAGE AS AN INTERVERNING VARIABLE AT GACOAN RESTAURANTS IN EAST KALIMANTAN - Surabi, Nur Fadilah; Fani, Julyia; Amanda, Zelmira; Rahmat, Rahmat; Margan, Choky; Rahmawati, Rahmawati (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2025)
This study aims to analyze the influence of Fear of Missing Out (FoMO) and Electronic Word of Mouth (EWoM) on consumer purchase intention with brand image as an intervening variable. The research was conducted on consumers of Gacoan Restaurant in East Kalimantan, involving 385 respondents selected through the Accidental Sampling technique. Data were collected using a Likert-scale questionnaire and analyzed using the SEM-PLS method. The results indicate that EWoM has a positive and significant effect on brand image and purchase intention, both directly and through the mediation of brand image. In contrast, FoMO shows a positive but not significant influence on brand image and purchase intention. These findings highlight the crucial role of EWoM in building a strong brand image to enhance consumer purchase intention. This study contributes to the digital marketing literature and can serve as a guide for restaurant managers in designing effective promotional strategies.